Earnings Management and Underpricing of IPOs on an Emerging Market - Lizińska , Joanna; Czapiewski, Leszek (Studia Oeconomica Posnaniensia, 2018)
The empirical design of this study concentrates on earnings management activities around initial public offerings of equity (IPOs). Previous studies for developed markets mostly concluded that many companies managed earnings around important company events. Such practices were especially aggressive around important corporate events, and the IPO is reputedly one of them. This study aims at the measurement of the pervasiveness of earnings management and describing its consequences for company short-term market pricing on an emerging market, mainly for Poland. Earning management was measured with discretionary accruals proxied with the application of cross sectional models. The empirical research provided evidence that earnings management practices were also reported for Polish IPO companies around IPO. However, strong differences in aggressive earnings management among IPO firms were revealed during the subperiods of stable or bull versus bear market. Earnings management approximated by discretionary accruals had informative power in explaining first-day IPO returns.